Springtime dandelion (Taraxacum officinale) control with seven postemergence herbicides applied at three anthesis stages - Raudenbush, Zane; Keeley, Steven J. (My University, 2015)
Although spring is not considered the optimal time for herbicidal control of most cool-season broadleaf weeds in turfgrass, spring applications are often required. Most new postemergence broadleaf herbicides combine several active ingredients, possibly resulting in synergistic, antagonistic, or additive effects. Therefore, as new herbicides become available, information is needed about their performance when applied in the spring. The objective of our study was to determine the effect of spring application timing on dandelion control with seven commercially available postemergence herbicides. Products were applied at their lowest labeled rate for dandelion control at three spring application timings, which coincided with dandelion anthesis stages (pre-, peak-, or post-bloom). A grid was used to determine percent dandelion control at several rating dates. The 2010 site had a denser turfgrass stand with smaller dandelions and was irrigated more frequently compared with the 2011 site. In 2010, all herbicides gave 98% or greater control at 30 days after treatment (DAT) when applied post-bloom; when applied pre- or peak-bloom, control was 80% or greater for all herbicides except for two products applied peak-bloom. At pre- and peak-bloom, products combining a protoporphyrinogen oxidase (PPO) inhibitor with a 2,4-D ester formulation were superior to most other herbicides. When evaluated at the end of the growing season in 2010, all herbicides provided 89% or greater control at all three timings. In 2011, with a less dense turfgrass stand, larger dandelions, and less frequent irrigation, control was more variable and shorter-lived among herbicides. When applied pre-bloom, all products containing 2,4-D provided 87% or greater control 60 DAT. Post-bloom application generally gave similar control to the pre-bloom timing. Peak-bloom application resulted in the poorest overall control at 60 DAT, but products combining a PPO inhibitor with a 2,4-D ester formulation performed better than most other herbicides. By the end of the season, dandelion regrowth caused reduced overall control at all timings, but overall control was poorest when applied at peak-bloom. In summary, peak-bloom applications should be avoided, especially if dandelion pressure is high. Products combining PPO inhibitors with ester forms of 2,4-D were most effective across all spring application timings. Products containing amine forms of 2,4-D may provide effective control if applied pre- or post-bloom.
Keywords: 2,4-D; Application timing; Broadleaf weed control; Carfentrazone-ethyl; Dicamba; Pyraflufen-ethyl